Pembinaan Model Konsepsi Dan Amalan Pentaksiran Guru - Abd. Rahman, Yusni (2014)

(untitled)
This is a survey research on Teacher’s Conceptions and Assessment Practices (TCoAP) involving 396 sample of teachers from 127 schools in Perak. The focus of the study was to evaluate the psychometric characteristics of TCoAP instrument through the development of the TCoAP model. The study also investigated the relationship between teachers’ conceptions and assessment practices. Kajian tinjauan terhadap Konsepsi dan Amalan Pentaksiran Guru (KAPG) melibatkan 396 orang guru sampel dari 127 buah sekolah di negeri Perak. Tumpuan kajian adalah untuk menilai ciri-ciri psikometrik instrumen melalui pembinaan model KAPG yang dibentuk. Kajian turut mengenal pasti hubungan di antara konsepsi dan amalan pentaksiran guru.